1971
DOI: 10.1139/e71-075
|View full text |Cite
|
Sign up to set email alerts
|

The Paleomagnetism of Diabase Dikes from the Grenville Province

Abstract: A paleomagnetic study was attempted of the diabase dike swarm intruding the Grenville structural province of the Canadian Shield. Both the alternating field and thermal demagnetization studies indicated that the dikes have varying degrees of stability of magnetization. Some dikes were shown to have stable primary component of magnetization. Microscopic observations indicated that, in most cases, the primary magnetic mineral titanomagnetite was altered to titanomaghemite, probably due to low temperature oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The first paleomagnetic study of the Grenville swarm (Murthy, 1971) showed that the dykes could be subdivided into three groups based on their magnetization direction after thermal and AF demagnetization: Group I with a generally steep down direction that is ubiquitous along the swarm, Group II with a steep negative inclination towards the SE found only in the eastern half of the swarm and Group III with a shallow down to the SE direction but with strong movement upon demagnetization from typical Group I directions, and mostly found in the western end of the swarm. Both Ti magnetite and Ti maghemite were reported, the latter especially so in Group I sites in which the characteristic component was identified as a PEF or older secondary component.…”
Section: Geological and Geophysical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The first paleomagnetic study of the Grenville swarm (Murthy, 1971) showed that the dykes could be subdivided into three groups based on their magnetization direction after thermal and AF demagnetization: Group I with a generally steep down direction that is ubiquitous along the swarm, Group II with a steep negative inclination towards the SE found only in the eastern half of the swarm and Group III with a shallow down to the SE direction but with strong movement upon demagnetization from typical Group I directions, and mostly found in the western end of the swarm. Both Ti magnetite and Ti maghemite were reported, the latter especially so in Group I sites in which the characteristic component was identified as a PEF or older secondary component.…”
Section: Geological and Geophysical Backgroundmentioning
confidence: 99%
“…The main first-order result is that characteristic directions are distributed along an approximate NW-SE great circle path, and include examples from all three directional groups defined by Murthy (1971) together with one that he did not find. The main components, designated A, B, C, C , D and E have the following directions:…”
Section: Paleomagnetism: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A rifting episode dating back to late Precambrian to early Paleozoic time is marked by arenites filling early graben structures (Hofmann, 1972;Kumarapeli, 1985), diabase dykes (∼700 million years; Murthy, 1971) intruding Grenvillian basement rocks, alkalic and carbonatite complexes (∼565 Ma; Gittins et al, 1967) intruding the graben floor at Lake Nipissing (Doig, 1970;Kumarapeli, 1985), and by the bimodal character of alkalic or transitional Tibbit Hill volcanic rocks (Hadrynian to early Cambrian; Pintson et al, 1985) in southern Québec.…”
Section: Geology and Tectonic Settingmentioning
confidence: 99%
“…, (Hargraves and Burt 1967); Fr, Frontenac Axis dikes ; Gd, Grenville diabase dikes (Murthy 1971); Gf, Grenville Front anorthosites (Palmer and Carmichael1973); Hb, Haliburton intrusions (Buchan and Dunlop 1976); In, Indian Head anorthosite (Murthy and Rao 1976); Me, Mealy Mountain anorthosite (Fahrig er al. 1974);Mg, Magnetawan metasediments (McWilliams and Dunlop 1975); Mr, Morin anorthosite (Irving et al 1974~); Ot, Ottawa basic intrusions ; St, Steel Mountain anorthosite (Murthy and Rao 1976); Tu, Tudor gabbro (Palmer and Carmichael 1973); Wi, Wilberforce pyroxenite (Palmer and Carmichael 1973); Ws, Whitestone intrusions (Ueno et al 1975).…”
Section: Apparent Polar Wander and Tectonics Grenville Paleopolesmentioning
confidence: 99%